Dynamic evaluation of water resource carrying capacity in Hainan Island based on improved TOPSIS model - Wang Wen; Yang Bo (E3S Web of Conferences)
Introducing a GIS based analysis matrix of inherent condition indicators and grading standards for engineering water supply, an improved TOPSIS model was used to evaluate the water resource carrying capacity of 17 cities and counties on Hainan Island. The results show a poor evaluation level of water resource carrying capacity in most cities and counties. There is a weakness of water supply capacity, as well as a high level of demand pressure for water resources. The main limiting factors for cities and counties with a rating of "Poor" are reflected in water use efficiency indicators. The water resource carrying capacity of the central and southern regions is better than that of the northeast region.